2011
DOI: 10.1080/09687769.2010.548506
|View full text |Cite
|
Sign up to set email alerts
|

How do e-book readers enhance learning opportunities for distance work-based learners?

Abstract: We report on the incorporation of e-book readers into the delivery of two distancetaught master's programmes in Occupational Psychology (OP) and one in Education at the University of Leicester, UK. The programmes attract work-based practitioners in OP and Teaching English to Speakers of Other Languages, respectively. Challenges in curriculum delivery included the need for more flexibility in the curricula, better access to essential readings and maximising the benefit of learners' limited study time. As part o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 7 publications
2
31
0
1
Order By: Relevance
“…Benefits for e-books include easily accessible, can be loaded into portable devices and hence remotely available. As a result students can have greater control over when and where learning takes place in the midst of work and family commitments [32]. Students suggested that he -Welcome and Introduction‖ or similar threads should be set up within groups which allows communication to be within small number of students.…”
Section: Discussionmentioning
confidence: 99%
“…Benefits for e-books include easily accessible, can be loaded into portable devices and hence remotely available. As a result students can have greater control over when and where learning takes place in the midst of work and family commitments [32]. Students suggested that he -Welcome and Introduction‖ or similar threads should be set up within groups which allows communication to be within small number of students.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive mapping interviews are effective in capturing people's views, perceptions and experiences and presenting complex ideas in a graphical way, and have been used successfully in other e-learning contexts (Armellini & Aiyegbayo, 2010;Nie, Armellini, Witthaus, & Barklamb, 2011;Russell, 2009). …”
Section: Open Learning 107mentioning
confidence: 99%
“…Increasing access to e-books is not without difficulties, including issues of copyright mentioned both in the literature (Nie et al, 2011) and by librarians surveyed in this study, preventing access to core texts on e-readers. A solution may be to encourage DLs to access e-material via personal e-readers, smart phones and other mobile reading devices.…”
Section: Provision Of Library Resourcesmentioning
confidence: 99%